O potrzebie nowego słownika odapelatywnych nazwisk Polaków – perspektywy badawcze - Matusiak-Kempa, Iza (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2022)
<span dir="ltr" style="left: calc(var(–scale-factor)*74.66px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02645);" role="presentation">The aim of the article is to <span dir="ltr" style="left: calc(var(–scale-factor)*185.91px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01065);" role="presentation">discuss the issues related to <span dir="ltr" style="left: calc(var(–scale-factor)*300.00px); top: calc(var(–scale-factor)*118.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00775);" role="presentation">identifying the etymology of <span dir="ltr" style="left: calc(var(–scale-factor)*74.92px); top: calc(var(–scale-factor)*132.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988099);" role="presentation">Polish surnames derived from appellatives. It also proposes a <span dir="ltr" style="left: calc(var(–scale-factor)*318.88px); top: calc(var(–scale-factor)*132.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.999182);" role="presentation">study containing a <span dir="ltr" style="left: calc(var(–scale-factor)*394.34px); top: calc(var(–scale-factor)*132.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02092);" role="presentation">more <span dir="ltr" style="left: calc(var(–scale-factor)*75.21px); top: calc(var(–scale-factor)*146.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00494);" role="presentation">thorough explication <span dir="ltr" style="left: calc(var(–scale-factor)*160.67px); top: calc(var(–scale-factor)*146.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.993018);" role="presentation">of the motivation <span dir="ltr" style="left: calc(var(–scale-factor)*231.08px); top: calc(var(–scale-factor)*146.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.990431);" role="presentation">behind the effects of word-formation <span dir="ltr" style="left: calc(var(–scale-factor)*379.24px); top: calc(var(–scale-factor)*146.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.991726);" role="presentation">that have <span dir="ltr" style="left: calc(var(–scale-factor)*75.22px); top: calc(var(–scale-factor)*160.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.04319);" role="presentation">been used as surnames. It is argued that the use of appropriate <span dir="ltr" style="left: calc(var(–scale-factor)*336.50px); top: calc(var(–scale-factor)*160.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02866);" role="presentation">methods for analys<span dir="ltr" style="left: calc(var(–scale-factor)*75.18px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03643);" role="presentation">ing personal proper names may significantly contribute <span dir="ltr" style="left: calc(var(–scale-factor)*307.34px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03957);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*318.49px); top: calc(var(–scale-factor)*174.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02833);" role="presentation">revealing the pragmatic <span dir="ltr" style="left: calc(var(–scale-factor)*75.34px); top: calc(var(–scale-factor)*188.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0323);" role="presentation">aspects of personal names created in the past. The first part of the text presents the <span dir="ltr" style="left: calc(var(–scale-factor)*74.93px); top: calc(var(–scale-factor)*202.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02797);" role="presentation">ways of describing the origin of the discussed names in the largest Polish dictionar<span dir="ltr" style="left: calc(var(–scale-factor)*75.18px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01077);" role="presentation">ies of anthroponyms. Its second part is devoted to <span dir="ltr" style="left: calc(var(–scale-factor)*278.46px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02514);" role="presentation">the presentation <span dir="ltr" style="left: calc(var(–scale-factor)*346.23px); top: calc(var(–scale-factor)*216.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00377);" role="presentation">of old nicknames <span dir="ltr" style="left: calc(var(–scale-factor)*74.63px); top: calc(var(–scale-factor)*230.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.00248);" role="presentation">(currently functioning as surnames) as messages of everyday communication <span dir="ltr" style="left: calc(var(–scale-factor)*386.12px); top: calc(var(–scale-factor)*230.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0028);" role="presentation">and ele<span dir="ltr" style="left: calc(var(–scale-factor)*75.20px); top: calc(var(–scale-factor)*244.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.986438);" role="presentation">ments of the vernacular. This part justifies the idea of compiling a <span dir="ltr" style="left: calc(var(–scale-factor)*337.10px); top: calc(var(–scale-factor)*244.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.994042);" role="presentation">dictionary of Polish <span dir="ltr" style="left: calc(var(–scale-factor)*75.34px); top: calc(var(–scale-factor)*258.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01733);" role="presentation">surnames based on <span dir="ltr" style="left: calc(var(–scale-factor)*154.66px); top: calc(var(–scale-factor)*258.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.993931);" role="presentation">appellatives which would make use of the tools of ethnolinguistic <span dir="ltr" style="left: calc(var(–scale-factor)*75.20px); top: calc(var(–scale-factor)*272.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.988563);" role="presentation">methodology, especially Ryszard Tokarski’s <span dir="ltr" style="left: calc(var(–scale-factor)*252.18px); top: calc(var(–scale-factor)*272.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.02944);" role="presentation">open definition. The last part of the text <span dir="ltr" style="left: calc(var(–scale-factor)*75.32px); top: calc(var(–scale-factor)*286.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01662);" role="presentation">presents a <span dir="ltr" style="left: calc(var(–scale-factor)*118.45px); top: calc(var(–scale-factor)*286.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01799);" role="presentation">proposal for a <span dir="ltr" style="left: calc(var(–scale-factor)*177.76px); top: calc(var(–scale-factor)*286.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.03627);" role="presentation">dictionary entry on <span dir="ltr" style="left: calc(var(–scale-factor)*259.39px); top: calc(var(–scale-factor)*286.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.0129);" role="presentation">the example of surnames derived from <span dir="ltr" style="left: calc(var(–scale-factor)*75.21px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.989915);" role="presentation">the appellative <span dir="ltr" style="left: calc(var(–scale-factor)*135.48px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(0.9568);" role="presentation">bystry [<span dir="ltr" style="left: calc(var(–scale-factor)*164.96px); top: calc(var(–scale-factor)*301.55px); font-size: calc(var(–scale-factor)*8.60px); font-family: serif; transform: scaleX(1.06921);" role="presentation">PL <span dir="ltr" style="left: calc(var(–scale-factor)*178.13px); top: calc(var(–scale-factor)*300.50px); font-size: calc(var(–scale-factor)*10.00px); font-family: serif; transform: scaleX(1.01422);" role="presentation">smart].